2007
DOI: 10.1111/j.1471-4159.2007.05090.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐linking of sites involved with alcohol action between transmembrane segments 1 and 3 of the glycine receptor following activation

Abstract: J. Neurochem. (2008) 104, 1649–1662. Abstract The glycine receptor is a member of the Cys‐loop, ligand‐gated ion channel family and is responsible for inhibition in the CNS. We examined the orientation of amino acids I229 in transmembrane 1 (TM1) and A288 in TM3, which are both critical for alcohol and volatile anesthetic action. We mutated these two amino acids to cysteines either singly or in double mutants and expressed the receptors in Xenopus laevis oocytes. We tested whether disulfide bonds could form be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 64 publications
4
37
0
Order By: Relevance
“…Our initial studies (Mihic et al, 1997, Wick et al, 1998 suggested that amino acids in TM regions 2 and 3 of these receptor subunits play a critical role in alcohol modu-lation of channel function, although TM1 and TM4 residues have also been implicated (Lobo et al, 2004(Lobo et al, , 2006(Lobo et al, , 2008. These data support the hypothesis that a water-filled cavity exists among the TM regions in which alcohols can act.…”
supporting
confidence: 73%
“…Our initial studies (Mihic et al, 1997, Wick et al, 1998 suggested that amino acids in TM regions 2 and 3 of these receptor subunits play a critical role in alcohol modu-lation of channel function, although TM1 and TM4 residues have also been implicated (Lobo et al, 2004(Lobo et al, , 2006(Lobo et al, , 2008. These data support the hypothesis that a water-filled cavity exists among the TM regions in which alcohols can act.…”
supporting
confidence: 73%
“…Studies designed to identify the NMDA receptor region containing the site of alcohol action found that the NMDA receptor C-terminal domain regulates ethanol sensitivity (Alvestad et al, 2003;Xu et al, 2011;Trepanier et al, 2012); however, this domain does not contain the primary site of alcohol action because truncation of the C-terminal domain does not abolish ethanol inhibition (Anders et al, 2000;Peoples and Stewart, 2000). Taken together with studies demonstrating the role of membraneassociated domains in NMDA receptor gating (Kohda et al, 2000;Jones et al, 2002;Sobolevsky et al, 2002a), these studies suggested that sites of ethanol action may be located in one or more of the membrane-associated (M) domains, as appears to be the case for alcohol and anesthetic sites on GABA A and glycine receptors (Mihic et al, 1997;Lobo et al, 2008;McCracken et al, 2010).…”
Section: Introductionmentioning
confidence: 70%
“…Because alcohol binding cannot be studied by traditional radiolabel binding, mutating critical amino acids to cysteine and irreversibly labeling them with thiol-specific alcohol analogs allowed the determination of specific amino acids involved in alcohol binding and action (Mascia et al, 2000). Subsequent research expanded these findings and identified critical amino acids in TM1 and TM4 (Lobo et al, 2008;McCracken et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…The isolation and injection of the X. laevis oocytes and the subsequent two-electrode voltage clamp recording from them has been described previously (Lobo et al, 2008).…”
Section: Electrophysiology In X Laevis Oocytesmentioning
confidence: 99%